含间隙的翅翼机构运动稳定性的研究 - 戴源源; 王大燕; 谢进; 陈永 (Jixie chuandong)
Based on the merits and demerits of methods used in the stability analysis,Floquet-Lyapunov theory is employed to analyze the stability of the flapping-wing mechanism with bearing clearance. The dynamic equation of motion for the mechanism is established by continuous contacting model. The results show that the periodic motion of the flapping-wing mechanism will be unstable when the clearance is larger than a certain value.